2001
DOI: 10.1038/sj.onc.1204966
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Myc and activating transcription factor 2 (ATF2): Myc prolongs the half-life and induces phosphorylation of ATF2

Abstract: Myc is a key regulator of cell growth, di erentiation and apoptosis, and a ects cell fate decisions by activating as well as by inhibiting the expression of cellular genes. Myc is a member of the basic region ± helix ± loop ± helix ± leucine zipper (b-HLH-Zip) class of transcription factors, which heterodimerizes with the Max protein and recognizes a consensus Myc binding motif.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…ATF2 ubiquitination, facilitated by its association with non‐active JNK (Fuchs et al., 1997), is dimerization dependent (Fuchs and Ronai, 1999) and is primarily targeted at the transcriptionally active form of ATF2, (Fuchs et al., 2000) thereby providing a mechanism to limit ATF2 transcriptional output. ATF2 stability and activity could be prolonged upon its association with c‐Myc (Miethe et al., 2001). In S. pombe , a single member of the SAPK family called Sty1/Spc1/Phh1 stimulates gene expression via the Atf1 transcription factor, which is similar to the human ATF2 factor, and which binds to closely related DNA sequences.…”
Section: Atf2 – the Transcription Factormentioning
confidence: 99%
“…ATF2 ubiquitination, facilitated by its association with non‐active JNK (Fuchs et al., 1997), is dimerization dependent (Fuchs and Ronai, 1999) and is primarily targeted at the transcriptionally active form of ATF2, (Fuchs et al., 2000) thereby providing a mechanism to limit ATF2 transcriptional output. ATF2 stability and activity could be prolonged upon its association with c‐Myc (Miethe et al., 2001). In S. pombe , a single member of the SAPK family called Sty1/Spc1/Phh1 stimulates gene expression via the Atf1 transcription factor, which is similar to the human ATF2 factor, and which binds to closely related DNA sequences.…”
Section: Atf2 – the Transcription Factormentioning
confidence: 99%
“…Previous studies have demonstrated that Zn-DIGP can knock-down transcription of the c-myc oncogene 3-fold or more in cell cultures . Given the important functions of c-myc in mediating melanoma metastasis, ,, we decided to evaluate the anti-metastatic activities of Zn-DIGP using an assay that mimics the hematogenous spread of malignant melanoma in vivo . C57BL/6 mice were intravenously injected into the tail vein with B16F10 cells, and after 20 days the animals were sacrificed and the number of lung metastases determined by visual inspection.…”
Section: Resultsmentioning
confidence: 99%
“…20 The c-myc oncogene encodes for a transcription factor that, together with ATF-2, plays an important role in proliferation, differentiation, and apoptosis of melanoma. 22 Abnormal c-Myc expression can lead to tumorigenesis, 23 and the inhibition of c-Myc in mouse models causes melanoma regression. 24 Given these results, we decided to evaluate the anti-metastatic activities of GPcs in vivo.…”
mentioning
confidence: 99%
“…One major role of ATF2 is to regulate the response of cells to stress signals [ 47 , 48 ]. Furthermore, in 2001, Miethe J et al [ 49 ] identified a crosstalk between Myc and activating transcription factor 2 (ATF2): Myc prolongs the half-life of ATF2 and causes increased phosphorylation of ATF2 at sites that have been shown to be crucial for the regulation of ATF2 activity [ 49 ]. Thus, ATF2 is activated by c-Myc on the protein level.…”
Section: Discussionmentioning
confidence: 99%